Challenges of modern universities and redefining educational paradigms in the age of globalization - Krasulja Nevena D.; Vasiljević Blagojević Milica R.; Radojević Ivana Z. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The subject of this review paper is to study the current state of modern universities, and show the challenges universities are facing in today's society, emphasizing the need to redefine educational paradigms due to the impact of globalization and neoliberalism. The paper aims to identify problems in the university system and provide solutions so that the focus is again directed towards essential knowledge. The methodological approach of this paper is reflected in the analysis of professional literature, research of case studies and analysis of university policies. The research results are identification of key challenges universities are facing today, as well as confirmation of the negative effects of the "publish or perish" policy in academic circles. The conclusion that emerges from all of the above is that implementing slow education can allow universities to return to their essence as centers of knowledge and deep educational values. These proposals aim to make the renewal of the education system more sustainable and directed towards long-term benefits for students and society as a whole.